The Influence of Principal Leadership and Work Motivation on Teacher Performance at Elementary Schools in Poigar District - Sagita Healthy Mongkol; Hetty Julita Tumurang; Marssel Michael Sengkey (PT. AHLAL PUBLISHER NUSANTARA, 2026)
The influence of principal leadership and teacher work motivation in elementary schools in Poigar district. This research seeks to assess the degree to which principal leadership and work motivation contribute to teacher performance in Poigar District elementary schools. A quantitative associative design was used in this study. The research subjects were 220 teachers in Poigar District. Observation was used as the data collection technique, and questionnaires using a Likert scale and documentation. Data on principal leadership, work motivation, and teacher performance were collected using a structured questionnaire. The data were analyzed utilizing descriptive statistical analysis, analysis prerequisite tests in the form of normality, linearity, multicollinearity, heteroscedasticity tests and continued with multiple regression analysis, t-test, f-test, and determination coefficient r. The results of the study showed 1) there was a significant influence of principal leadership on teacher performance with a sig. 0.01 <0.05 and 7.149 > 1.971, so it was concluded that it was accepted. 2) there was an influence of teacher work motivation on teacher performance with a sig. 0.03 <0.05 and 7.013 > 1.971, so it was concluded that it was accepted. 3) Both principal leadership and teacher work motivation contribute to teacher performance with a sig. 004 < 0.05 and a value of 29.934 > 3.04, then accepted, with the outcomes of the coefficient of determination showing that principal leadership as well as work motivation contribute 60.8%. Thus, it may be inferred that principal leadership as well as work motivation significantly influence teacher performance at Poigar District Elementary School.t_hitung t_tabel H_1 t_hitung t_tabel H_2 F_hitung F_tabel H_3 Keywords: principal leadership, work motivation, teacher performance, elementary school, quantitative associative Abstrak Pengaruh kepemimpinan kepala sekolah disertai motivasi kerja guru di sekolah dasar di kecamatan Poigar. Penelitian ini dimaksudkan guna mencari tahu pengaruh kepemimpinan kepala sekolah disertai motivasi kerja pada kinerja guru di Sekolah Dasar Kecamatan Poigar. Studi ini mengadopsi pendekatan kuantitatif yang jenis penelitiannya asosiatif. Subjek penelitiannya ialah 220 guru di Kecamatan Poigar. Teknik pengumpulan data adalah melalui observasi, kuesioner menggunakan skala Likert dan dokumentasi. Instrumen penelitian berupa kuesioner mengukur data kepemimpinan kepala sekolah, kinerja guru, dan motivasi kerja. Data dianalisisnya mengadopsi analisis statistik deskriptif, uji prasyarat analisisnya mencakup uji normalitas, linearitas, multikolinearitas, heteroskedastisitas, dilanjutkan dengan analisis regresi berganda, uji t, uji f, dan juga koefisien determinasi r. temuan penelitian membuktikan 1) ada pengaruh cukup signifikan dari kepemimpinan kepala sekolah pada kinerja guru dengan sig. 0.01 < 0.05 dan 7.149 > 1.971, sehingga disimpulkan diterima. 2) ada pengaruh motivasi kerja guru pada kinerja guru dengan sig. 0.03 < 0.05 dan 7.013 > 1.971, alhasil disimpulkan diterima. 3) Kinerja guru terpengaruhi oleh kepemimpinan kepala sekolah, motivasi kerja guru dengan sig. 004 < 0.05 dan nilai 29.934 > 3.04, kemudian diterima, dengan hasil koefisien determinasi memperlihatkan bahwasanya kepemimpinan dari kepala sekolah serta motivasi kerja berkontribusi 60.8%. Dengan demikian, dapat disimpulkan bahwasanya kepemimpinan kepala sekolah dan motivasi kerja memiliki pengaruh yang signifikan terhadap kinerja guru di Sekolah Dasar Kecamatan Poigar.t_hitung t_tabel H_1 t_hitung t_tabel H_2 F_hitungF_tabelH_3 Kata Kunci: kepemimpinan kepala sekolah, motivasi kerja, kinerja guru, sekolah dasar, kuantitatif asosiatif